Exploring the Therapeutic Potenital of the Leaderless Enterocins K1 and EJ97 in the Treatment of Vancomycin-Resistant Enterococcal Infection - Reinseth, Ingvild; Tønnesen, Hanne H.; Carlsen, Harald; Diep, Dzung B. (Frontiers in Microbiology, 2021)
The membrane-bound protease Eep is an important virulence factor in pathogenic enterococci. The protein is involved in stress response via the RIP pathway which is crucial for pathogenic enterococci to evade host immune attacks during infection. Eep serves also as a receptor for the bacteriocins enterocin K1 and enterocin EJ97. The bacteriocins kill Enterococcus faecium and E. faecalis respectively, and their antibiotic resistant derivatives including vancomycin resistant enterococci (VRE). This functional duality of Eep makes these two enterocins very promising as options in the prospective treatment of enterococcal infections because wildtype enterococcal cells (with an intact Eep) are sensitive to the bacteriocins while bacteriocin-resistant-mutants (without a functional Eep) become less virulent. As a first step to explore their therapeutic potential in the treatment of systemic enterococcal infections, we investigated the compatibility of the bacteriocins with human blood, and the phenotypic changes of eep-mutants toward different stress conditions. We found that the bacteriocins were compatible with blood, as they did not cause haemolysis and that the bacteriocins retained most of their antibacterial effect when incubated in blood. The bacteriocins were autoclavable which is a crucial criterium for the development of parenteral administration. Eep-mutants, which became resistant to the bacteriocin were, as expected, less capable to withstand stress conditions such as exposure to lysozyme and desiccation. Further, their ability to chain, a trait implicated in niche adaptation as well as being necessary for genetic transfer via conjugation, was also severely affected. Together, these results indicate that the bacteriocins are promising for treatment of VRE infection.